Applying "First Principles of Instruction" as a design theory of the flipped classroom: Findings from a collective study of four secondary school subjects. (March 2018) - Lo, Chung Kwan; Lie, Chi Wai; Hew, Khe Foon
Abstract: The flipped classroom approach is a type of technology-enhanced pedagogy that has grown popular in education settings. An increasing number of empirical studies have evaluated this approach, but there is still no adequate theoretical framework for guiding the design and implementation of flipped classrooms. Furthermore, few such studies have been conducted in secondary school contexts, and the effects of flipped classrooms have not been adequately compared with those of non-flipped classrooms. This study aims to address these research gaps by applying the meta design theory "First Principles of Instruction" to design our flipped classroom approach. A two-stage study was conducted in two secondary schools, involving a total of 382 students and five teacher participants from four subject areas, namely mathematics, physics, Chinese language, and information and communication technology (ICT). Based on the experience of the pilot study (Study 1), we refined our flipped classroom model and examined its efficacy through a quasi-experimental design in the main study (Study 2). Although the students in the flipped ICT course had learning outcomes similar to those of students in the non-flipped ICT course, the levels of student achievement in the other three courses (i.e., mathematics, physics, and Chinese language) were improved after flipping, with a small to medium-sized effects. The design, benefits, and challenges of the model are discussed. We conclude by making several recommendations for practice, and suggesting ideas for further research. Highlights: The design of flipped classrooms was grounded in the First Principles of Instruction. Two-stage study was conducted in two secondary schools for refinement and evaluation. The refined model promoted student achievement in mathematics, physics, and Chinese language.